Modeling ozone plumes observed downwind of New York City over the North Atlantic Ocean during the ICARTT field campaign - S.-H. Lee (Atmospheric Chemistry and Physics, 2011)
Transport and chemical transformation of well-defined New York City (NYC) urban plumes over the North Atlantic Ocean were studied using aircraft measurements collected on 20–21 July 2004 during the ICARTT (International Consortium for Atmospheric Research on Transport and Transformation) field campaign and WRF-Chem (Weather Research and Forecasting-Chemistry) model simulations. The strong NYC urban plumes were characterized by carbon monoxide (CO) mixing ratios of 350–400 parts per billion by volume (ppbv) and ozone (O3) levels of about 100 ppbv near New York City on 20 July in the WP-3D in-situ and DC-3 lidar aircraft measurements. On 21 July, the two aircraft captured strong urban plumes with about 350 ppbv CO and over 150 ppbv O3 (~160 ppbv maximum) about 600 km downwind of NYC over the North Atlantic Ocean. The measured urban plumes extended vertically up to about 2 km near New York City, but shrank to 1–1.5 km over the stable marine boundary layer (MBL) over the North Atlantic Ocean. The WRF-Chem model reproduced ozone formation processes, chemical characteristics, and meteorology of the measured urban plumes near New York City (20 July) and in the far downwind region over the North Atlantic Ocean (21 July). The quasi-Lagrangian analysis of transport and chemical transformation of the simulated NYC urban plumes using WRF-Chem results showed that the pollutants can be efficiently transported in (isentropic) layers in the lower atmosphere (<2–3 km) over the North Atlantic Ocean while maintaining a dynamic vertical decoupling by cessation of turbulence in the stable MBL. The O3 mixing ratio in the NYC urban plumes remained at 80–90 ppbv during nocturnal transport over the stable MBL, then grew to over 100 ppbv by daytime oxidation of nitrogen oxides (NOx = NO + NO2) with mixing ratios on the order of 1 ppbv. Efficient transport of reactive nitrogen species (NOy), specifically nitric acid (HNO3), was confirmed through the comparison of the CO/NOy ratio in photochemically fresh and aged NYC plumes, implying the possibility of long-range transport of O3 over the stable MBL over the North Atlantic Ocean in association with NOx regeneration mechanism. The impact of chemical initial and boundary conditions (IC/BCs) on modelled O3 urban plumes was investigated in terms of the background O3 level and the vertical structure of the urban plumes. Simulations with dynamic ("time-variant") chemical IC/BCs enhanced the O3 level by 2–12 ppbv on average in the atmospheric layer below 3 km, showing better agreement with the observed NYC plumes and biomass-burning plumes than the simulation with prescribed static IC/BCs. The simulation including MOZART-4 chemical IC/BCs and Alaskan/Canadian wildfire emissions compared better to the observed O3 profiles in the upper atmospheric layer (>~3 km) than models that only accounted for North American anthropogenic/biogenic and wildfire contributions to background ozone. The comparison between models and observations show that chemical IC/BCs must be properly specified to achieve accurate model results.